Market Share as a Measure of Performance: Conceptual Issues and Financial Accountability for Marketing Activities within a Firm - Khantimirov, Denis (Journal of Research in Marketing (ISSN: 2292-9355), 2017)
Given the ever increasing pressure on marketers to demonstrate the value of their activities to the firm, the present literature review focuses on market share as a performance measure and its relationship to profitability. The paper attempts to contribute to the area of marketing performance measurement in several ways: a) in order to enhance the ability to measure marketing performance for future empirical studies, the refined conceptualization of the market share metric is presented; b) the conducted review of market share – profitability link synthesizes the findings and reveals a rather fragmented and contradicting nature of empirical studies; as a result, several research questions are formulated to (1) help academic scholars in guiding their efforts for future research and to (2) assist practitioners in improving their ability to account for marketing’s contribution to the overall organizational performance and maintain marketing’s stature within organizations.